The Need for Knowledge Translation in Chronic Pain - James L Henry (Pain Research and Management)
One in five Canadians suffers from some form of persistent or chronic pain. The impact on individual lives, families and friends, the health services sector and the economy is huge. Reliable evidence is available that the burden of persistent pain can be markedly reduced when available knowledge is applied. Bridging the quality chasm between chronic pain and the care process will require a unique confluence of opinion from all stakeholders committed within a focused community of practice to address the impact of pain. Various levels of success in this regard have been demonstrated when there is exchange, synthesis and ethically sound application of research findings within a complex set of interactions among researchers and knowledge users. It is now critical to accelerate the capture of the benefits of research for Canadians through improved health, more effective and responsive services and products, and a strengthened health care system to bring about health reform and health care reform across Canada as it pertains to the one in five Canadians living with chronic, disabling pain. The overarching outcome of such an initiative needs to be promoted to sustain a balanced portfolio of curiosity-and needs-based research, which along with existing knowledge, can be mobilized and applied for the benefit of Canadians, the health care system and the economy.